Optimization of Backup Power System for A House in Libya Using HOMER Pro - Mosbah, Fathi; Iqbal, M. Tariq (Journal of Electronics and Electrical Engineering, 2026)
Power outages are a persistent and widespread issue in many developing countries, significantly affecting economic development, public health, education, and overall quality of life. These outages, often referred to as "load shedding," occur due to a combination of inadequate infrastructure, poor maintenance, limited energy production, and mismanagement of resources. The increasing frequency of power outages and the growing interest in renewable energy technologies have driven the adoption of hybrid backup power systems for residential applications. However, the economic performance of such systems under subsidized fuel and electricity prices has not been sufficiently examined. This paper presents an optimal sizing and economic analysis of a hybrid photovoltaic (PV), battery, and diesel generator system designed to supply residential loads in Libya during grid outages lasting from 1 to 7 hours. The system is modelled and optimized using HOMER Pro software. Since electricity, gas, and diesel are subsidized for the public in Libya, the optimization is conducted for three different load cases: 2,912.7, 4,855.89, and 7,538.434 kWh/yr. A comparison of the economic performance of the three residential backup power system configurations under varying power outage durations, along with sensitivity analyses, is conducted to evaluate system performance and the impact of variations in diesel and renewable energy component costs. Despite subsidized electricity and fuel prices, the results indicate that incorporating renewable energy with energy storage, in addition to a diesel generator, is more economical and reliable for residential backup power systems in Libya. Furthermore, integrating renewable energy systems reduces generator operating hours, thereby lowering maintenance costs and pollution. Renewable energy penetration generally increases with outage duration, with the medium-load case achieving the highest renewable fraction of 36.1% during extended outages.